Coordenação pedagógica – um espaço do acompanhamento da documentação docente do ensino fundamental anos iniciais - Miné, Valdete Aparecida do Amaral (2026)
This thesis aims to understand how pedagogical coordination follows the documentary trajectory of teachers in Elementary Education – Early Years, articulating individual and collective aspects of teaching practices and the conception of resources that promote the development of students’ Algebraic Thinking. It is justified by the scarcity of studies supported by the Documentary Approach to Didactics in the Early Years, aligned with the Brazilian National Common Core Curriculum (BNCC) and the Municipal Curriculum of Atibaia – SP, responding to the need for reflective teacher education. The central argument emphasizes that pedagogical coordination, through the Reflective Investigative Methodology, enhances documentary genesis, transforming resources for the transition from Arithmetic/Algebraic Thinking and for teachers’ professional development, through Rabardel’s processes of instrumentation and instrumentalization. Theoretically, it integrates the Documentary Approach to Didactics, Luc Trouche, Gueudet, and Pepin, with Algebraic Thinking and the Theory of Conceptual Fields, highlighting documentary trajectories. The methodology adopted in this thesis is a qualitative approach using the Reflective Investigative Methodology in a municipal school in Atibaia, São Paulo, focusing on four teachers, through incubation processes and analysis of the task “The Matchsticks,” following the five principles of the Reflective Investigative Methodology. The investigation sought to answer the following question: “How can pedagogical coordination play a role in monitoring the documentary trajectory of teachers in training, in order to foster the development of Algebraic Thinking in students of Elementary Education – Early Years?”. The results revealed that the mediations among teacher–resource–teacher favor the transition from Arithmetic to Algebraic Thinking, partial patterns, and generalizations, enriching documentary trajectories and reflective practices, with suggestions for continuing teacher education